DELONE AND MCLEAN ON THE SUCCESS OF LEARNING MANAGEMENT SYSTEMS IN DISTANCE LEARNING - Adhi Susano; Khasanah (International Journal of Social Science, 2022)
This study aims to see how the level of success of a learning management system used by a private university that runs the learning process with distance learning, where the method used in this study is a quantitative method using the Delone and McLean approach. system quality has no effect on user intensity with an R square value of 2.6%, system quality affects user satisfaction with an R square value of 19.3%, information quality does not affect user intensity with an R square value of 0.1%, Information quality affects user satisfaction with an R square value of 28.6%, service quality does not affect user intensity with an R square value of 0.4%, service quality affects user satisfaction with an R square value of 49.8%. usage satisfaction has no effect on user intensity with an R square value of 0%, use satisfaction affects benefits with an R square value of 53.6%, use affects user satisfaction with an R square value of 16.9%, use affects benefits with an R square value of 20.6%. benefits affect use with an R square value of 20.6%, benefits affect use satisfaction with an R square value of 53.6%.